Penguatan Karakter Guru melalui Reaktualiasai Cerita Rakyat bagi Guru Sekolah Dasar - Ibrahim, Nini; Yanti, Prima Gusti; Tarmini, Wini; Hidayatullah, Ahmad (Empowerment, 2023)
Teachers are key in shaping students' character, and it is important for them to prepare themselves and enhance their own character before instilling it in their students. Folklore plays a crucial role in realizing this goal. Therefore, community service activities are conducted with the aim of strengthening teachers' character through an understanding of these values. Seminars and mentoring procedures are implemented as methods for conducting these activities. The results of these activities reveal the support of the community service team, and positive evaluation outcomes have provided significant benefits in strengthening teachers' characters, including their ability to recognize character values, develop creativity in writing folklore stories, and relate folklore to current social issues. In conclusion, these activities have successfully improved the understanding and skills of teachers in using folklore as an effective tool for character development.Guru merupakan kunci utama dalam pembentukan karakter peserta didik. Guru perlu mempersiapkan diri dan meningkatkan karakternya menjadi lebih baik sebelum menanamkan kepada siswa. Dalam hal ini, cerita rakyat memiliki peranan penting dalam merealisasukan hal tersebut. Untuk itu, kegiatan pengabdian masyarakat dilakukan dengan tujuan untuk memperkuat karakter guru melalui pemahaman nilai tersebut. Prosedur seminar dan pendampingan dilakukan sebagai metode pelaksanaan kegiatan. Hasil kegiatan ini mengungkapkan adanya dukungan tim pengmas dan hasil evaluasi yang positif memberikan manfaat yang signifikan dalam penguatan karakter guru-guru, termasuk kemampuan mengenali nilai-nilai karakter, mengembangkan kreativitas dalam menulis cerita rakyat, dan mengaitkan cerita rakyat dengan permasalahan sosial aktual. Simpulannya yaitu kegiatan ini telah berhasil meningkatkan pemahaman dan keterampilan guru-guru dalam menggunakan cerita rakyat sebagai alat efektif dalam penguatan karakter.